Pengembangan Model Pembelajaran Group Investigation Media Vido Story Pokok Bahasan Keseimbangan Lingkungan Untuk Meningkatkan Berpikir Kritis Siswa - Sofiyati Awaliya; Hernik Pujiastutik (BIO-PEDAGOGI, 2017)
Tuban Regency is one of the areas that holds the potential of nature, this can be seen from the number of large factories established in Tuban Regency. The existence of this large factory causes changes in the surrounding environmental balance. Based on the results of observation of learning in SMA Muhammadiyah 03 Bancar class X on the subject of environmental balance is still conventional with the lecture method and discussion of this matter leads to less interesting and boring learning therefore there needs to be a development of learning models where students can engage in a social solution Namely the Group Investigation learning model (GI). The purpose of this research is to develop a model of learning by using the environment as a learning medium that is packaged in the form of video story to cultivate students' critical thinking skills. The students' critical thinking ability can be measured from aspects of identifying problems, interpreting, giving relevant ideas and drawing conclusions. This type of research is a research development, which is the development of a learning model that is very appropriate for the material of environmental balance class X semester even, the resulting draft then validated by two experts and one teacher as a user. The results showed the average validation of two experts and one user is 83.529% which indicates valid criteria and is worthy of use. From the results of small-scale test results amounted to 15 students who analyzed with the normalized gain obtained N gain> 0.7. These results indicate that there is a significant improvement in critical thinking of the students so that it can be concluded that the development of this learning model is very valid and feasible to be applied to improve critical thinking of the students.